Тепловые характеристики хроматина, ядер и ДНК мышей BalB и С3НА, получивших ионы Ni²⁺ - Патиашвили, Л.Д.; Монаселидзе, Д.Р.; Чанчадашвили, З.И.; Читадзе, Г.Ш.; Маджагаладзе, Г.В.; Ломидзе, Э.М. (Биополимеры и клетка, 1987)
С помощью высокочувствительной дифференциальной сканирующей микрокалориметрии, предназначенной для исследования сложных биологических систем, исследованы термодинамические характеристики хроматина непосредственно в составе клеток и ДНК хроматина и свободном состоянии. Установлено, что канцерогенный ион Ni²⁺ повреждает ДНК хроматина in vivo независимо от того, имеет опухоль вирусное или химическое происхождение. За допомогою високочутливої диференційної сканувальної мікрокалориметрії, призначеної для дослідження складних біологічних систем, проаналізовано термодинамічні характеристики хроматину безпосередньо у складі клітин і ДНК хроматину та у вільному стані. Встановлено, що канцерогенний іон Ni²⁺ пошкоджує ДНК хроматину in vivo незалежно від того, має пухлина вірусне чи хімічне походження. The method of differential scanning microcalorimelry (DSM) is used to find those minute changes which arise in active chromatin DNA of tumour cells and nuclei as a result of Ni²⁺ ions penetration into the DNA structure. Chromatin native structure is established to be considerably destructed by the incorporation of Ni²⁺ ions in chromatin DNA of cells. The comparative analysis of melting process of DNA isolated from tumour cells of mice which were given and not given Ni²⁺ ions showed that the changes in the chromatin structure are closely related to the DNA double helix damage.